1999
DOI: 10.1155/1999/86213
|View full text |Cite
|
Sign up to set email alerts
|

Collision‐Induced E(0g+)−D(0u+) State‐to‐State Energy Transfer in I2

Abstract: Electronic energy transfer in the E(0g+) D(0+) system of I2 is investigated in an experiment, where single rovibrational quantum states are prepared, single collision conditions prevail, and the final states have been determined from dispersed fluorescence. In I (E) X (X Ar, N2, 02) the collisional decay is found to be governed by minimum energy transfer. With (X I2) an anomalous behaviour is found for the initially prepared E, v 8, J 56 level, which is tentatively ascribed to vibrational excitation of the col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 18 publications
3
26
0
Order By: Relevance
“…The spectra shown in the upper and lower traces in Fig. 4 reproduce those reported by Ubachs et al [5,6] and Bibinov et al [4], respectively, and which were displayed in Fig. 4 of Ref.…”
Section: Vibrational Distribution Following Ase and Collisional Energsupporting
confidence: 83%
See 3 more Smart Citations
“…The spectra shown in the upper and lower traces in Fig. 4 reproduce those reported by Ubachs et al [5,6] and Bibinov et al [4], respectively, and which were displayed in Fig. 4 of Ref.…”
Section: Vibrational Distribution Following Ase and Collisional Energsupporting
confidence: 83%
“…There were less marked differences between the two earlier data sets for (v = 9, 13 and 15) of the E0 þ g ð 3 P 2 Þ state [4,6]. However, for all three levels there was an enhancement of the transfer with the largest FCF in the study where ASE transfer was observed from (v = 8) [6].…”
Section: Vibrational Distribution Following Ase and Collisional Energmentioning
confidence: 63%
See 2 more Smart Citations
“…M other IP statesÞ non-adiabatic transitions induced by collisions with molecular partners different from the I 2 (X) is very scarce. Data on kinetics of the transitions from the E state to the D one induced by collisions with N 2 and CF 4 are only available in the literature [7,[12][13][14]. Besides, very recently, Hutchison et al studied I 2 ðE !…”
Section: Introductionmentioning
confidence: 99%